Nutrition for Generation Z: Navigating Challenges and Opportunities in Modern Diets - Azmi, Sefiani Dwi (Pt. Anagata Sembagi Education, 2024)
Generation Z, born from the mid-1990s to the early 2010s, is deeply influenced by digital advancements, which shape their dietary behaviors. While social media and technology provide abundant nutrition information, they also expose Generation Z to the allure of fast food and processed snacks, challenging their efforts to maintain a balanced diet. This struggle is exacerbated by hectic lifestyles and pervasive advertising targeting unhealthy foods. Consequently, nutrition-related issues like obesity and eating disorders are on the rise. However, Generation Z holds potential to drive positive dietary changes, fueled by their health consciousness and tech-savvy nature. Innovative education programs and technology can play pivotal roles in promoting healthier eating habits. This mixed-methods research, focusing on urban and semi-urban areas in Indonesia, aims to comprehensively explore Generation Z's diets. Findings reveal a varied dietary landscape, highlighting the prevalence of breakfast consumption but a lack of nutritional balance. Bridging the gap between nutrition knowledge and practice necessitates interactive education and policy interventions, vital for fostering healthier dietary habits among Generation Z.